A study on Anti-diabetic effects of ethanolic extract of Pomelo (Citrus Maxima Linn) and Glibenclamide on blood glucose level of diabetic rats - Noor, SB; Afrin, S; Alima, F; Nahar, k; Sultana, S (Journal of Dhaka National Medical College & Hospital, 2022)
Background: Diabetes mellitus is a one of the major public health problem adversely affecting health and socio-economic status of people at both national and global level. Objective: To evaluate the effects of ethanolic extract of Pomelo (Citrus maxima linn) fruit juice on blood glucose level in alloxan induced diabetic rats. Methods: This experimental study was carried out in two parts on 30 albino rats. In experiment-1; 12 rats were divided into 2 groups; each comprising of 6 rats. Group-I: Normal non-diabetic rats are fed with normal feed only and Group-II: Normal non-diabetic rat were fed with normal feed with Citrus maxima extract for 21 days. In experiment-II, 18 rats were divide into three groups; Group III (diabetic control), Group IV (experimental group) and Group V (standard drug group). To induce diabetic, these 18 rats were injected alloxan 120 mg/kg body weight intraperitoneally. Then group III and IV were treated with the Citrus maxima ethanol extract and Glibenclamide respectively from day! to day 21. Results: Blood glucose level of group IV decreased significantly (p<0.05) from 12.10-13.30 to 7.00-7.50 mmol/l. Blood glucose level of group V also decreased significantly (p<0.05) from 12.50-13.50 to 6.50 to7.90 mmol/l.Difference of blood glucose results between group IV and V was not statistically significant. Conclusion: The ethanolic extract of Citrus maxima has shown significant activity like Glibenclamideto reduce blood glucose in hyperglycemic rats. J. Dhaka National Med. Coll. Hos. 2022; 28 (01): 34-41